The Impact of Global and Domestic Factors on Nickel Company Stock Prices in Indonesia (2020-2023) - Indriani Putri; Yoyok Prasetyo; Nani Ernawati (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2025)
This study aims to empirically examine the effect of world nickel prices, global economic policy uncertainty, inflation, interest rates, and rupiah exchange rates on the stock prices of nickel companies in Indonesia for the period 2020-2023.  This study uses secondary data from several sources, namely the Indonesia Stock Exchange (IDX), London Metal Exchange, Economic Policy Uncertainty, Central Bureau of Statistics, and Bank Indonesia.   The purposive sampling method was used for sampling in this study so that the sample studied consisted of 6 nickel companies in Indonesia in a monthly period during the period 2020-2023. The variables in this study were analyzed using multiple regression methods. The results showed that the variables of world nickel prices, global economic policy uncertainty, inflation, interest rates, and rupiah exchange rates simultaneously affect the stock price of nickel companies. Then the variables of world nickel prices, global economic policy uncertainty, and interest rates partially affect the stock price of nickel companies. At the same time, the variables of inflation and rupiah exchange rate have no partial effect on the stock price of nickel companies. Keywords: World Nickel Prices; Global Economic Policy Uncertainty; Inflation; Interest Rates; Rupiah Exchange Rate